RISK MANAGEMENT IN MULTI STOREY BUILDING CONSTRUCTION - Radhakrishnan; Selvan, K G (International Journal of Research -GRANTHAALAYAH, 2018)
The Construction Industry is the source for widespread employment for people of all walks of life, next only to Agriculture. The industry is picking up very well now after the shake of demonetisation. The builders have also understood the importance of RERA and majority of the builders are ensuring total compliance to it. The GST which was initially looked at as a blow is being viewed in its proper perspective. The current trend in the construction field is to offer “ready to occupy homes”. This is, basically, due to two reasons. Large numbers of builders are in the field doing construction, in almost the entire city and the outskirts. This healthy competition has necessitated offering maximum benefits to customers and whatever possible to retain them in their fold. In a way, the customers are being attracted so nicely that they have to only pay the initial amount at the time of booking, forget about the bother of EMI,